Global Transcriptomic Analysis During Murine Pneumonia Infection Reveals New Virulence Factors in Acinetobacter baumannii. (25th August 2020) - Martínez-Guitián, Marta; Vázquez-Ucha, Juan C; Álvarez-Fraga, Laura; Conde-Pérez, Kelly; Vallejo, Juan A; Perina, Alejandra; Bou, Germán; Poza, Margarita; Beceiro, Alejandro
Abstract: Background: Infections caused by multidrug-resistant pathogens such as Acinetobacter baumannii constitute a major health problem worldwide. In this study we present a global in vivo transcriptomic analysis of A. baumannii isolated from the lungs of mice with pneumonia infection. Methods: Mice were infected with A. baumannii ATCC 17978 and AbH12O-A2 strains and the total bacterial RNA were analyzed by RNA sequencing. Lists of differentially expressed genes were obtained and 14 of them were selected for gene deletion and further analysis. Results: Transcriptomic analysis revealed a specific gene expression profile in A. baumannii during lung infection with upregulation of genes involved in iron acquisition and host invasion. Mutant strains lacking feoA, mtnN, yfgC, basB, hisF, oatA, and bfnL showed a significant loss of virulence in murine pneumonia. A decrease in biofilm formation, adherence to human epithelial cells, and growth rate was observed in selected mutants. Conclusions: This study provides an insight into A. baumannii gene expression profile during murine pneumonia infection. Data revealed that 7 in vivo upregulated genes were involved in virulence and could be considered new therapeutic targets. Abstract : This study describes the transcriptomic response of A. baumannii in murine pneumonia infection and demonstrates the key role of selected genes in the ability of this pathogen to cause infection. This allowed us to identify potential novel therapeutic targets.